The Quality of Selected Online Learning Platforms and Their Effect on Education in the Sultanate of Oman - Ghaith Abdulsattar A. Jabbar Alkubaisi (Hindawi Limited, 2021)
The COVID-19 pandemic has led to the largest interruption in education around the world, affecting some 1.6 billion students. Classroom education stopped, to be replaced by online e-learning platforms. In higher education, e-learning is made available through recorded lectures, with online platforms becoming a significant part of the overall system. This study aims to identify the quality of online learning platforms, applying a set of criteria from the perspective of faculty members and students in higher education institutions in the Sultanate of Oman. The descriptive approach is used and the researchers collected data through a questionnaire directed at 32 faculty members and 104 students. The results show that e-learning programs are generally of high quality, from the perspective of the participants, but with statistically significant differences according to the type of program.